The Elusive Eden A New History of California - Richard B. Rice; William A. Bullough; Richard J. Orsi; Mary Ann Irwin (New York The McGraw-Hill, 2002)
This text charts the historical development of California, beginning with the evolution of the landscape and climate and the arrival of the first inhabitants, the Indians, through social, political and environmental controversies, to the present day.
Keywords: California -- History. California. Social life -- History